Students' Views on Using Powtoon for Vocabulary Learning: Persepsi Siswa Terhadap Penggunaan Powtoon dalam Pembelajaran Kosakata - Saputra, Bagas Wahyu Dwi; Taufiq , Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates students' perceptions of using Powtoon as a digital tool for learning vocabulary related to physical appearance. General Background: In an era where technology integration in education is vital, understanding student engagement with digital learning tools is essential. Specific Background: While various multimedia tools exist, limited research has focused specifically on Powtoon in the context of vocabulary acquisition. Knowledge Gap: This study aims to fill the gap by examining how Powtoon influences student learning experiences in vocabulary retention. Aims: The primary objective is to explore how students perceive the use of Powtoon for learning vocabulary associated with physical appearance. Results: Through in-depth interviews with five participants and classroom observations, findings indicate that students generally hold positive views about Powtoon, citing its engaging animations and interactive features as enhancing the learning experience. Novelty: This research contributes to the literature by providing insights into the effectiveness of Powtoon as an interactive learning medium. Implications: The results suggest that integrating multimedia tools like Powtoon can significantly improve students' understanding and retention of vocabulary, highlighting its potential as a valuable resource in vocabulary instruction. Highlights: Positive Engagement: Students reported that Powtoon's engaging animations and interactive features made learning enjoyable and effective. Improved Retention: Participants noted that visualizing and interacting with vocabulary helped enhance their understanding and memory of the terms. Valuable Resource: The study highlights Powtoon as a beneficial tool for vocabulary instruction, supporting the integration of multimedia in language learning. Keywords: Powtoon, vocabulary learning, student perceptions, digital tools, education.